1991
DOI: 10.1192/pb.15.8.465
|View full text |Cite
|
Sign up to set email alerts
|

Police referrals — a crisis intervention approach

Abstract: Recently, concern has been expressed by mental health professionals, MIND, and the police regarding the management of Section 136 referrals, which at present varies according to the local psychiatric services available. In the majority of London Metropolitan Boroughs a person deemed to be in need of care and control is taken first to a police station where the necessary documentation is completed and then transported, often a considerable distance, to a mental hospital for the purpose of assessment. This can r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…The mean age for both men and women detained under S136 is typically reported to be between 32 and 41 years, with some variation among different ethnic groups also reported. 4,13,23,24 Fahy et al 12 reviewed all S136 admissions to two psychiatric hospitals in south west London over a two-year period in 1984 and 1985. They reported that black individuals were, on average, significantly younger than their white counterparts, a finding that has since been replicated in other studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age for both men and women detained under S136 is typically reported to be between 32 and 41 years, with some variation among different ethnic groups also reported. 4,13,23,24 Fahy et al 12 reviewed all S136 admissions to two psychiatric hospitals in south west London over a two-year period in 1984 and 1985. They reported that black individuals were, on average, significantly younger than their white counterparts, a finding that has since been replicated in other studies.…”
Section: Resultsmentioning
confidence: 99%
“…1–3 Such behaviour typically deviates from what is accepted by society but often does not constitute an offence. 4 In the United Kingdom (UK), one option available to any police officer upon becoming aware of such behaviour is to detain the individual under Section 136 (hereafter S136) of the Mental Health Act (1983), 5 which states: If a constable finds in a place to which the public have access a person who appears to him to be suffering from mental disorder and to be in immediate need of care or control, the constable may, if he thinks necessary to do so in the interests of that person or for the protection of other persons, remove that person to a place of safety… A person removed to a place of safety under this section may be detained there for a period not exceeding 72 hours for the purpose of enabling him to be examined by a registered medical practitioner and to be interviewed by an approved social worker and of making any necessary arrangements for his treatment or care. A place of safety, as defined in the Act, refers to residential accommodation provided by a local services authority, a hospital as defined by the Act, a police station, a mental health nursing home or residential nursing home for mentally disordered persons, or any other suitable place the occupier of which is willing to temporarily receive the individual. S136 is the only section of the Act whereby one person – acting without medical evidence or training – has the authority to deprive another person of his or her personal liberty.…”
Section: Introductionmentioning
confidence: 99%
“…One alternative model of service has described crisis intervention teams assessing such patients in the police station [34]. This seemed to reduce admission rates.…”
Section: "Situational Crisis"mentioning
confidence: 99%
“…Responding to people presenting with mental health issues is a difficult area of police work not simply confined to matters of enforcement (Riley et al, 2011a;Morgan et al, 1991). Reports from across the globe suggest that the level of contact between the police and the mentally ill continues to increase (College of Policing 2015;Clifford, 2010;Coleman and Cotton, 2010;Moore, 2010).…”
Section: Introductionmentioning
confidence: 99%